Study of clinical profile, complications and management of acquired cholesteatoma in pediatric age group: a retrospective study - ., Rajneesh; Pawar, Shradha; Valse, Dinesh; Doddamani, Anil Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic suppurative otitis media when delayed of early treatment results in complications. And the present study is conducted to evaluate the complications and management of acquired cholesteatoma in pediatric age group. Aim of the study was to highlight important aspects and paradigms of clinical profile of pediatric cholesteatoma, its complications and management Methods: A retrospective audit of total 15 cases of acquired paediatric cholesteatoma with complications were studied aged 4-14 years, for a period of 2 years from January 2018 to 2020, at a tertiary referral Centre and teaching hospital. An analysis was made about the clinical profile of pediatric acquired cholesteatoma, its complications and the overall management. Results: The male to female ratio was found to be 2:3. The most common presenting feature was foul smelling otorrhea, decreased hearing and earache with headache, fever in complicated cases. 9 cases among 15 (60%) had complications both intracranial and extra cranial. Surgery was the main modality of management of these conditions. Intraoperatively the major findings were cholesteatoma and granulation in the attic and mesotympanum with erosion of scutum. Conclusions: Acquired cholesteatoma in children is more aggressive than adults, and likely to present with advanced disease with ossicular chain involvement. Patients with unreliable follow up and limited access to operating theatre, Canal Wall Down mastoidectomy is an optimal management for complete exposure and removal of cholesteatoma.